Analysis Legal Protection Towards Wife as a Victim in Case Domestic Violence - Febriansyah, Ferry Irawan; Andriansyah, Lucky (International Journal of Law and Society, 2022)
The purpose of this study was to obtain data and explain the factors that cause domestic violence. In addition, it is also to explain how far the development of legal protection for wives as victims of domestic violence. This study uses a normative legal research method with a legal approach. Data collected directly from the community is called primary data, while data through library sources is called secondary data, laws and regulations, scientific publications, journals, and research-related papers. Research findings are presented in the form of a systematic description. To evaluate the collected data, a normative analysis approach will be used. Factors causing domestic violence. First, there is a disparity between men and women, both at home and in public. Second, domestic violence is associated with power dynamics between husband and wife and with gender inequality in society. Legal protection for wives who are victims of husband violence. Forms of legal protection for women victims of violence are contained in the Law on the Elimination of Domestic Violence (Law No. 23 of 2004). Forms of legal protection include victims' rights in the form of: protection from family, police, prosecutors, courts, advocates, or other parties temporarily or based on protection orders from courts, health services according to medical needs, and special treatment. Legal protection for perpetrators of physical violence, psychological violence, and sexual violence consists of criminal sanctions.